If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 28 = 26m + -39 Combine like terms: -7 + 28 = 21 21 = 26m + -39 Reorder the terms: 21 = -39 + 26m Solving 21 = -39 + 26m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-26m' to each side of the equation. 21 + -26m = -39 + 26m + -26m Combine like terms: 26m + -26m = 0 21 + -26m = -39 + 0 21 + -26m = -39 Add '-21' to each side of the equation. 21 + -21 + -26m = -39 + -21 Combine like terms: 21 + -21 = 0 0 + -26m = -39 + -21 -26m = -39 + -21 Combine like terms: -39 + -21 = -60 -26m = -60 Divide each side by '-26'. m = 2.307692308 Simplifying m = 2.307692308
| 4x+13=-46 | | x+2x+(6x+1)=37 | | x+95=3x-37 | | -5x=2y | | X+17+x+9=12 | | 10x=-105x+38 | | -1=6x-5x+8 | | 18=49-2 | | 3000m= | | x+2x+(6x+3)=48 | | lx+-2l=2 | | A=500(1+0.08)20 | | 2(x-21)+3(x-3)=44 | | (3x-12)=60 | | (20a+30)+5a=180 | | 4x+4x-7=2(4x+7) | | -7x-7=-70 | | x+2x+(5x+2)=18 | | 6x+3=5(x+8)-3 | | 1+x=2x-5 | | -4=n-3-4 | | 5x+5-x-3=3x-x+8 | | 6+x+3-2x=6 | | (.66x*2)+(3x)=150 | | 12-6(-2)=24 | | 4n+17+(n-2)=180 | | 12x+8y=28 | | -4p=n-3-4 | | x+2x+(3x+2)=20 | | 4x-3(2x)=-6 | | 10*2=490 | | -3.25*-1.56= |